Preparation method of heteroatom-doped phenolic resin nano-adsorbent and its application in selective separation of palladium
By introducing nitrogen and selenium into the phenolic resin adsorbent and using high-speed stirring preparation technology, the problem of low adsorption capacity and selectivity of palladium ions in the existing adsorption technology is solved, and efficient extraction of palladium ions and sustainable resource recovery is achieved.
Patent Information
- Application Number
- CN202410753628.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-12
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-06-12
AI Technical Summary
The existing adsorption technology has problems with low adsorption capacity and selectivity in the recovery of precious metal palladium, especially in low concentrations and complex environments, which are difficult to effectively extract palladium ions.
Using a fast controllable preparation method based on high-speed stirring, N-doped phenolic resin nano-adsorbent (RF-H) and N-Se co-doped phenolic resin nano-adsorbent (Se-RF-H) are prepared by introducing nitrogen and selenium doping technology to improve the adsorption capacity of palladium ions.
It significantly improves the selectivity and adsorption capacity of the adsorbent, can efficiently extract palladium ions in complex environments, is suitable for the recovery of low-concentration precious metals, and the preparation method is fast and controllable, reducing costs.
Smart Images

Figure CN118515830B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of adsorption and separation functional materials, and relates to the preparation of a heteroatom-doped phenolic resin adsorbent for selectively separating palladium, and in particular to a rapid and controllable preparation method based on high-speed stirring assistance and its application in selective adsorption and separation of palladium ions. Background Art
[0002] The precious metal palladium is widely used in jewelry, finance, electronics, aerospace, military, catalysis and medical fields due to its excellent physical and chemical properties. It is an extremely important economic and strategic resource. With the rapid growth of demand for precious metals and the limited nature of ore resources, the contradiction between supply and demand has become increasingly prominent. Electronic waste, due to its high content of precious metals, has become an attractive source of recycling. However, most electronic waste is not properly recycled, resulting in resource waste and environmental pollution. Studies have shown that palladium resources are extremely scarce in nature (the concentration in the earth's crust is only 0.015ppm), and the content of palladium in discarded electronic equipment (300g t -1 ) is much higher than natural ore (<10g t -1 ). This makes e-waste an “urban mine” that has yet to be mined.
[0003] At present, the main methods for extracting precious metals from electronic waste include precipitation, ion exchange, extraction, membrane separation, electrolysis and adsorption. Among these methods, adsorption is considered to be a technology with great potential due to its low cost, high extraction rate and easy continuous operation. However, current adsorption technology still faces challenges when facing low concentrations of precious metals, complex competing ions and extremely acidic environments.
[0004] Although common resorcinol-formaldehyde resins (phenolic resins) have been widely used in industry, this traditional material still has some limitations in specific areas, especially in the recovery of precious metals. First, common phenolic resins often show low adsorption capacity and selectivity when adsorbing precious metals, especially palladium. Due to the limitations of their chemical structure, these resins often have difficulty in achieving effective recognition and selective adsorption of specific precious metal ions when dealing with complex systems containing multiple metal ions. Therefore, there is an urgent need to develop a new adsorbent that can quickly and selectively extract the precious metal palladium from electronic waste leachate under the premise of being environmentally friendly and highly selective.
[0005] In the development of adsorption technology, the demand for efficient and controllable preparation of adsorbents is growing. An ideal adsorbent should have high adsorption capacity, excellent selectivity, good chemical stability, and be able to operate stably in complex environments. However, traditional adsorbent preparation methods are often limited by long synthesis time, complex steps, and low cost-effectiveness. Therefore, the development of a fast and controllable adsorbent preparation method has become an important issue in the industry. Summary of the invention
[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to overcome the problems of complicated preparation steps, low adsorption capacity and selectivity of existing palladium ion adsorbents, and to provide a method for rapidly and controllably preparing a novel phenolic resin adsorbent based on heteroatom doping. The nitrogen element in ammonia water is used as a necessary condition for rapid prototyping, and selenium compounds are used as key monomers. By utilizing their strong affinity with precious metal ions, an N-doped phenolic resin adsorbent (RF-H) and an N, Se co-doped phenolic resin adsorbent (Se-RF-H) are rapidly and controllably prepared by high-speed stirring.
[0007] In order to achieve the above technical purpose, the technical solution adopted by the present invention is as follows:
[0008] A method for preparing an N-doped phenolic resin nano-adsorbent, comprising the following steps:
[0009] Step A1: Add ammonia water to a certain proportion of ethanol-water solution, add resorcinol, ultrasonically disperse, then add formaldehyde aqueous solution, and then insert a high-speed stirrer to stir at a certain speed r 1 Stir the reaction for a certain time t 2 The solid was separated by centrifugation, washed with water and ethanol several times to obtain the product N-doped phenolic resin nanoadsorbent RF-H, and then placed in a vacuum oven to be fully dried.
[0010] In step A1, the usage ratio of ammonia water, ethanol, deionized water, resorcinol and formaldehyde aqueous solution is 35-150 μL: 1-6 mL: 1-6 mL: 10-70 mg: 35-150 μL;
[0011] Wherein, the mass percentage concentration of the formaldehyde aqueous solution is 37.0-40.0%,
[0012] Speed of high speed agitator 1 5000-15000rpm, reaction time t 2 3-7min.
[0013] A method for preparing a N, Se co-doped phenolic resin nano-adsorbent, comprising the following steps:
[0014] Step B1: Preparation of bis(4-hydroxyphenyl)selenide monomer
[0015] First, add selenium powder to chloroform A and disperse it by magnetic stirring. Then add a mixture of sulfonyl chloride and chloroform B. After stirring evenly, add a mixture of phenol and anhydrous ether and stir until clear and transparent. Continue to react at room temperature for a period of time. 1 After that, a certain concentration of Na 2 CO 3 The solution was stirred until no bubbles were generated, and the organic phase was separated using a separatory funnel. The organic solvent was removed by rotary evaporation and purified by column chromatography to finally obtain a golden solid, i.e., bis(4-hydroxyphenyl)selenide monomer;
[0016] Step B2: Preparation of N, Se co-doped phenolic resin nanoadsorbent
[0017] Ammonia water is added to a certain proportion of ethanol-water solution, resorcinol and the bis(4-hydroxyphenyl)selenide monomer synthesized in step B1 are added, ultrasonic dispersion is performed, and then a certain amount of formaldehyde aqueous solution is added, and a high-speed stirrer is immediately inserted to stir at a certain speed r 2 Stir the reaction for a certain time t 3 The solid was separated by centrifugation, washed with water and ethanol several times to obtain the product N, Se co-doped phenolic resin nanoadsorbent (Se-RF-H), and placed in a vacuum oven to be fully dried.
[0018] In step B1, the ratio of the selenium powder, chloroform A, sulfonyl chloride, chloroform B, phenol and anhydrous ether is 1.98-7.90 g: 50-200 mL: 3.38-13.50 g: 50-200 mL: 4.70-18.80 g: 50-200 mL; the reaction time t 1 2-4h, Na 2 CO 3 The mass concentration of the solution is 10.50-42.00wt%.
[0019] In step B2, the ratio of the amount of ammonia water, ethanol, deionized water, resorcinol, formaldehyde solution and bis(4-hydroxyphenyl)selenide is 35-150 μL: 1-6 mL: 1-6 mL: 5-20 mg: 35-150 μL: 12-50 mg;
[0020] The mass percentage concentration of the formaldehyde aqueous solution is 37.0-40.0%, and the speed of the high-speed stirrer is 2 5000-15000rpm, reaction time t 3 3-7min.
[0021] The N-doped phenolic resin nano-adsorbent or the N, Se co-doped phenolic resin nano-adsorbent prepared by the invention is used for adsorbing palladium ions.
[0022] Beneficial effects of the present invention:
[0023] Solve the problem of precious metal recycling: Since the content of precious metal palladium in electronic waste is relatively high, the adsorbent of the present invention is designed and prepared for the precious metals in electronic waste. This helps to efficiently recycle precious metals in electronic waste and meets the demand for efficient recycling of resources.
[0024] Improved selectivity and adsorption capacity of the adsorbent: Traditional phenolic resins may exhibit low adsorption capacity and selectivity when adsorbing precious metals, while the present invention introduces selenium compounds as key monomers, which achieve high selectivity for palladium and improved adsorption capacity through their strong affinity with precious metal ions.
[0025] Utilizing heteroatom doping technology: The present invention uses a heteroatom doping method, that is, introducing nitrogen and selenium elements in the process of preparing the phenolic resin adsorbent, thereby enhancing the performance of the adsorbent. This doping technology helps to regulate the physicochemical properties of the adsorbent and improve its adsorption capacity for palladium ions under specific conditions.
[0026] Rapid and controllable preparation method: The present invention uses a rapid and controllable preparation method assisted by high-speed stirring, and achieves rapid preparation of the new adsorbent by adjusting the reaction conditions and time. This helps to improve preparation efficiency, reduce costs, and promote industrial production.
[0027] Applicable to complex environments and low-concentration precious metals: Traditional adsorption technology faces challenges when facing low-concentration precious metals, complex competing ions and extremely acidic environments. The adsorbent provided by the present invention still performs well under these conditions and has good stability and adaptability.
[0028] In summary, the present invention has significant economic benefits in the field of precious metal recovery and can effectively address the waste of precious metal resources and environmental pollution in electronic waste. At the same time, by introducing a new adsorbent and a rapid preparation method, the present invention has important innovative significance in the field of adsorption technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The scanning electron microscope images and particle size distribution diagrams of RF-H prepared at different rotation speeds in Example 1 are shown.
[0030] Figure 2 In which, ab are the scanning electron microscope images and transmission electron microscope images of RF-H obtained at a rotation speed of 10000 rpm in Example 1, and de are the scanning electron microscope images and transmission electron microscope images of Se-RF-H obtained at a rotation speed of 10000 rpm.
[0031] Figure 3This is a nitrogen adsorption-desorption curve diagram of the Se-RF-H adsorbent prepared in Example 1.
[0032] Figure 4 This is the infrared spectra of the RF-H and Se-RF-H adsorbents prepared in Example 1.
[0033] Figure 5 The figure shows the effect of pH value on the adsorption capacity of palladium ions by the Se-RF-H adsorbent prepared in Example 1.
[0034] Figure 6 The adsorption kinetics of palladium ions by the Se-RF-H adsorbent prepared in Example 1 and its model fitting curve.
[0035] Figure 7 The effect of temperature on the adsorption equilibrium of palladium ions by the Se-RF-H adsorbent prepared in Example 1 and its model fitting curve.
[0036] Figure 8 This is the adsorption selectivity of the Se-RF-H adsorbent prepared in Example 1.
[0037] Fig. 9 This is the adsorption regeneration performance of the Se-RF-H adsorbent prepared in Example 1. DETAILED DESCRIPTION
[0038] In the specific implementation of the present invention, the recognition performance evaluation is carried out according to the following method: the static adsorption experiment is used to complete. The adsorption capacity of 2.0 mg of Se-RF-H for palladium ions in the pH range of 1.0-4.0 is tested, and the content of palladium ions after adsorption is determined by inductively coupled plasma emission spectrometer, and the optimal adsorption pH is determined according to the results; secondly, the effect of adsorption time on the adsorption capacity of Se-RF-H is studied, and the data are fitted, calculated and analyzed using Pseudo first-order model, Pseudo second-order model, etc.; to study the maximum adsorption capacity of Se-RF-H, we conducted an adsorption equilibrium test in the range of palladium ion concentration of 100-500ppm, and fitted the adsorption data using Langmuir model and Freundlich model, and calculated the adsorption capacity according to the results; and selected several other common metal ions in electronic waste as competitive adsorbents to study the selective adsorption performance of Se-RF-H; finally, its adsorption regeneration performance was tested.
[0039] The present invention will be further described below in conjunction with specific implementation examples.
[0040] Embodiment 1:
[0041] (1) Preparation of N-doped phenolic resin nanoadsorbent
[0042] 70 μL of ammonia water was added to a 1 mL:6 mL ethanol-water solution, 70 mg of resorcinol was added, and ultrasonic dispersion was performed. Then 70 μL of formaldehyde aqueous solution was added, and a high-speed stirrer was inserted and stirred at 10,000 rpm for 5 min. The solid was separated by centrifugation, and the product N-doped phenolic resin nanoadsorbent (RF-H) was obtained after washing with water and ethanol several times, and then placed in a vacuum oven to be fully dried.
[0043] (2) Preparation of bis(4-hydroxyphenyl)selenide monomer
[0044] First, add 3.96g of selenium powder to 100mL of chloroform and disperse it by magnetic stirring. Then add a mixture of 6.75g of sulfuryl chloride and 100mL of chloroform, stir evenly, then add a mixture of 9.4g of phenol and 100mL of anhydrous ether, stir until clear and transparent, continue to react at room temperature for 3h, and then add 21wt% Na 2 CO 3 The solution was stirred until no bubbles were generated, and the organic phase was separated using a separatory funnel, and the organic solvent was removed by rotary evaporation. Purification by column chromatography finally obtained a golden solid.
[0045] (3) Preparation of N, Se co-doped phenolic resin nanoadsorbent
[0046] 70 μL of ammonia water was added to a 1 mL:6 mL ethanol-water solution, and 10 mg of resorcinol and 25 mg of the monomer synthesized in (1) were added and ultrasonically dispersed. Subsequently, 70 μL of formaldehyde aqueous solution was added and a high-speed stirrer was inserted and stirred at 10,000 rpm for 5 min. The solid was separated by centrifugation and washed with water and ethanol several times to obtain the product N, Se co-doped phenolic resin nanoadsorbent (Se-RF-H), which was placed in a vacuum oven and fully dried.
[0047] Figure 1 The following are the SEM images of RF-H prepared at different stirring speeds. By comparison, it can be found that without stirring, the particle size of the product is uneven and the preparation time is longer. When the rotation speed is 10000rpm, the particle size of the product is the most uniform. The particle size distribution range is expanded by increasing or decreasing the rotation speed.
[0048] Figure 2 Shown are scanning electron microscope images and transmission electron microscope images of RF-H (a, b) and Se-RF-H (c, d) prepared in Example 1. It can be seen that unlike RF-H, Se-RF-H has an obvious core.
[0049] Figure 3The figure shows the nitrogen adsorption-desorption curve of Se-RF-H prepared in Example 1, and its specific surface area is about 25.41 m 2 ·g -1 .
[0050] Figure 4 The infrared spectra of RF-H and Se-RF-H prepared in Example 1 are shown. Since they have similar structures, there is no significant difference between them, except that Se-RF-H has a peak at 2900 cm -1 The absorption peak of C-Se was increased, confirming the successful introduction of Se element.
[0051] Embodiment 2:
[0052] (1) Preparation of N-doped phenolic resin nanoadsorbent
[0053] 35 μL of ammonia water was added to a 2 mL:5 mL ethanol-water solution, 10 mg of resorcinol was added, and ultrasonic dispersion was performed. Then 35 μL of formaldehyde aqueous solution was added, and a high-speed stirrer was immediately inserted and stirred at 5000 rpm for 3 min. The solid was separated by centrifugation, and the product N-doped phenolic resin nanoadsorbent (RF-H) was obtained after washing with water and ethanol several times, and then placed in a vacuum oven to be fully dried.
[0054] (2) Preparation of bis(4-hydroxyphenyl)selenide monomer
[0055] First, add 1.98g of selenium powder to 50mL of chloroform and disperse it by magnetic stirring. Then add a mixture of 3.38g of sulfuryl chloride and 50mL of chloroform, stir evenly, then add a mixture of 4.7g of phenol and 50mL of anhydrous ether, stir until clear and transparent, continue to react at room temperature for 2h, and then add 10.5wt% Na 2 CO 3 The solution was stirred until no bubbles were generated, and the organic phase was separated using a separatory funnel, and the organic solvent was removed by rotary evaporation. Purification by column chromatography finally obtained a golden solid.
[0056] (3) Preparation of N, Se co-doped phenolic resin nanoadsorbent
[0057] 35 μL of ammonia water was added to a 2 mL:5 mL ethanol-water solution, and 5 mg of resorcinol and 12 mg of the monomer synthesized in (1) were added and ultrasonically dispersed. Subsequently, 35 μL of formaldehyde aqueous solution was added and a high-speed stirrer was inserted and stirred at 5000 rpm for 3 min. The solid was separated by centrifugation and washed with water and ethanol several times to obtain the product N, Se co-doped phenolic resin nanoadsorbent (Se-RF-H), which was placed in a vacuum oven and fully dried.
[0058] Embodiment 3:
[0059] (1) Preparation of N-doped phenolic resin nanoadsorbent
[0060] 150 μL of ammonia water was added to a 3 mL:4 mL ethanol-water solution, 70 mg of resorcinol was added, and ultrasonic dispersion was performed. Then 150 μL of formaldehyde aqueous solution was added, and a high-speed stirrer was inserted and stirred at 15000 rpm for 7 min. The solid was separated by centrifugation, and the product N-doped phenolic resin nanoadsorbent (RF-H) was obtained after washing with water and ethanol several times, and then placed in a vacuum oven to be fully dried.
[0061] (2) Preparation of bis(4-hydroxyphenyl)selenide monomer
[0062] First, add 7.9g of selenium powder into 200mL of chloroform and disperse it by magnetic stirring. Then add a mixture of 13.5g of sulfuryl chloride and 200mL of chloroform, stir evenly, then add a mixture of 18.8g of phenol and 200mL of anhydrous ether, stir until clear and transparent, continue to react at room temperature for 4h, then add 42wt% Na 2 CO 3 The solution was stirred until no bubbles were generated, and the organic phase was separated using a separatory funnel, and the organic solvent was removed by rotary evaporation. Purification by column chromatography finally obtained a golden solid.
[0063] (3) Preparation of N, Se co-doped phenolic resin nanoadsorbent
[0064] 150 μL of ammonia water was added to a 3 mL:4 mL ethanol-water solution, and 20 mg of resorcinol and 50 mg of the monomer synthesized in (1) were added and dispersed by ultrasonication. Subsequently, 150 μL of formaldehyde aqueous solution was added and a high-speed stirrer was inserted and stirred at 15000 rpm for 7 min. The solid was separated by centrifugation and washed with water and ethanol several times to obtain the product N, Se co-doped phenolic resin nanoadsorbent (Se-RF-H), which was placed in a vacuum oven and fully dried.
[0065] Embodiment 4:
[0066] Accurately weigh 4 portions of 2 mg of Se-RF-H prepared under the conditions described in Example 1, add them to 5 mL of palladium ion solution with pH values of 1, 2, 3, and 4 and a concentration of 100 mg / L, place them on a shaker at 25°C for adsorption for 2 hours, and collect the supernatant. The residual palladium ion concentration in the solution is detected by inductively coupled plasma emission spectrometry (ICP), and three parallel experiments are performed. Figure 5 As shown, when the pH value is equal to 2, the adsorption capacity of Se-RF-H prepared in Example 1 reaches the maximum value, which is determined by the existence form of Pd(II) and the charge properties of the adsorbent surface.
[0067] Embodiment 5:
[0068] Weigh 8 portions of 2 mg of RF-H and 9 portions of 2 mg of Se-RF-H accurately, add them to 5 mL of a 100 mg / L, pH 2 palladium ion solution, place them on a shaker at 25°C and adsorb for 5, 10, 15, 20, 30, 60, 120, 240, 360 min, and collect the supernatant. The remaining palladium ion concentration in the solution was detected by inductively coupled plasma emission spectrometry (ICP), and three parallel experiments were performed. Figure 6 The adsorption kinetics of Pd(Ⅱ) by Se-RF-H and RF-H prepared in Example 1 are shown. RF-H reaches adsorption equilibrium within 120 min, while Se-RF-H only reaches adsorption equilibrium within 60 min. The equilibrium adsorption capacity of Se-RF-H is significantly higher than that of RF-H. The data are fitted, calculated and analyzed using Pseudo first-order model and Pseudo second-order model, respectively.
[0069] Embodiment 6:
[0070] Weigh 6 portions of 2 mg of Se-RF-H accurately, add them to 5 mL of palladium ion solution (pH 2) with concentrations of 100, 200, 300, 400, and 500 mg / L, respectively, and place them on a shaker for adsorption at 25°C for 1 hour, collect the supernatant; place them on a shaker for adsorption at 35°C for 1 hour, collect the supernatant; place them on a shaker for adsorption at 45°C for 1 hour, collect the supernatant. The residual palladium ion concentration in the solution was detected by inductively coupled plasma emission spectrometry (ICP), and three parallel experiments were performed. Figure 7 The adsorption isotherm of Pd(II) by Se-RF-H prepared in Example 1 is shown. The Langmuir model and the Freundlich model are used to fit the adsorption data, and the effect of temperature on the adsorption capacity is explored. Within the test temperature range, the adsorption capacity increases with increasing temperature.
[0071] Embodiment 7:
[0072] Accurately weigh 2 mg of RF-H and Se-RF-H, add 5 mL of simulated electronic waste leaching mixed solution containing 50 mg / L of Pd(Ⅱ), Ca(Ⅱ), Cu(Ⅱ), Fe(Ⅲ), K(Ⅰ), Mg(Ⅱ), Na(Ⅰ), Ni(Ⅱ), and Zn(Ⅱ), place on a shaker at 25°C for adsorption for 1 hour, collect the supernatant, and use inductively coupled plasma emission spectrometer (ICP) to detect the residual concentration of various ions in the solution. Three parallel experiments were performed. Figure 8As shown, in the presence of numerous interfering ions, the RF-H and Se-RF-H prepared in Example 1 still have the highest adsorption capacity for Pd(Ⅱ), which is much greater than the adsorption capacity for metal ions such as Ca(Ⅱ), Cu(Ⅱ), Fe(Ⅲ), K(Ⅰ), Mg(Ⅱ), Na(Ⅰ), Ni(Ⅱ), and Zn(Ⅱ), and the adsorption selectivity of Se-RF-H for Pd(Ⅱ) is significantly better than that of RF-H.
[0073] Embodiment 8:
[0074] Accurately weigh 2 mg of Se-RF-H, add 5 mL of palladium ion solution with a concentration of 100 mg / L and a pH value of 2, place it on a shaker at 25°C for adsorption for 1 hour, take the supernatant and remove the solution, wash with deionized water, add 5 mL of eluent prepared with 1 mol / L thiourea and 0.1 mol / L hydrochloric acid, continue to place it on a shaker for desorption for 1 hour, then centrifuge to collect the adsorbent, remove the solution, wash with deionized water and dry. This is one cycle, and a total of five cycles are performed. The remaining palladium ion concentration in the solution is detected by inductively coupled plasma emission spectrometry (ICP), and three parallel experiments are performed. Fig. 9 As shown, the Se-RF-H prepared in Example 1 still has a high adsorption capacity after 5 adsorption-desorption cycle experiments, indicating that it has good adsorption regeneration performance and can maintain good adsorption capacity for Pd(II) during cyclic use.
[0075] Note: The above embodiments are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention; therefore, although this specification has described the present invention in detail with reference to the above embodiments, a person skilled in the art should understand that the present invention can still be modified or replaced by equivalents; and all technical solutions and improvements thereof that do not depart from the spirit and scope of the present invention should be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a heteroatom-doped phenolic resin nano-adsorbent, characterized in that: The heteroatom-doped phenolic resin nano-adsorbent includes N-doped phenolic resin nano-adsorbent RF-H or N, Se co-doped phenolic resin nano-adsorbent Se-RF-H; in, The N-doped phenolic resin nano-adsorbent RF-H is prepared by using ammonia water and resorcinol as main raw materials and a high-speed stirring method; the specific preparation steps are as follows: Step A1: adding ammonia water to a certain proportion of ethanol-water solution, adding resorcinol, ultrasonically dispersing, then adding formaldehyde aqueous solution, and then inserting a high-speed stirrer, stirring at a certain speed r1 for a certain time t2, separating the obtained solid by centrifugation, washing with water and ethanol several times to obtain the product N-doped phenolic resin nanoadsorbent RF-H, and placing it in a vacuum oven to fully dry; In step A1, the dosage ratio of the ammonia water, ethanol, deionized water, resorcinol and formaldehyde aqueous solution is 35-150 μL: 1-6 mL: 1-6 mL: 10-70 mg: 35-150 μL; wherein the mass percentage concentration of the formaldehyde aqueous solution is 37.0-40.0%; N, Se co-doped phenolic resin nano-adsorbent Se-RF-H is prepared by high-speed stirring method with ammonia water, resorcinol and bis(4-hydroxyphenyl) selenide monomer as main raw materials; the specific preparation steps are as follows: Step B1: Preparation of bis(4-hydroxyphenyl)selenide monomer First, selenium powder is added to chloroform A and dispersed by magnetic stirring, then a mixture of sulfonyl chloride and chloroform B is added, and after stirring evenly, a mixture of phenol and anhydrous ether is added and stirred until clear and transparent. After continuing to react for a period of time t1 at room temperature, a certain concentration of Na2CO3 solution is added dropwise until no bubbles are generated, an organic phase is separated by a separatory funnel, the organic solvent is removed by rotary evaporation, and purification is performed by column chromatography to finally obtain a golden solid, i.e., a bis(4-hydroxyphenyl)selenide monomer; Step B2: Preparation of N, Se co-doped phenolic resin nanoadsorbent Ammonia water is added to a certain proportion of ethanol-water solution, resorcinol and the bis(4-hydroxyphenyl) selenide monomer synthesized in step B1 are added, ultrasonic dispersion is performed, and then a certain amount of formaldehyde aqueous solution is added, and a high-speed stirrer is immediately inserted, and the reaction is stirred at a certain speed r2 for a certain time t3, and the obtained solid is separated by centrifugation, and the product N, Se co-doped phenolic resin nanoadsorbent (Se-RF-H) is obtained after washing with water and ethanol for several times, and the product is placed in a vacuum oven to be fully dried; In step B2, the ratio of ammonia water, ethanol, deionized water, resorcinol, formaldehyde aqueous solution and bis(4-hydroxyphenyl)selenide is 35-150 μL: 1-6 mL: 1-6 mL: 5-20 mg: 35-150 μL: 12-50 mg; wherein the mass percentage concentration of the formaldehyde aqueous solution is 37.0-40.0% The speed of high-speed stirring is not less than 5000rpm.
2. The preparation method according to claim 1, characterized in that In step A1, the rotation speed r1 of the high-speed stirrer is 5000-15000 rpm, and the reaction time t2 is 3-7 min.
3. The preparation method according to claim 1, characterized in that: In step B1, the usage ratio of the selenium powder, chloroform A, sulfonyl chloride, chloroform B, phenol and anhydrous ether is 1.98-7.90 g: 50-200 mL: 3.38-13.50 g: 50-200 mL: 4.70-18.80 g: 50-200 mL.
4. The preparation method according to claim 1, characterized in that: In step B1, the reaction time t1 is 2-4 hours, and the mass concentration of the Na2CO3 solution is 10.50-42.00 wt%.
5. The preparation method according to claim 1, characterized in that: In step B2, the rotation speed r2 of the high-speed stirrer is 5000-15000 rpm, and the reaction time t3 is 3-7 min.
6. Use of the heteroatom-doped phenolic resin nano-adsorbent prepared by the preparation method according to claim 1 for adsorbing palladium ions.